Plant immune inducer ZNC promotes rutin accumulation and enhances resistance to Botrytis cinerea in tomato - Haipeng Zhao; Xiangyu Ding; Xiaomeng Chu; Haimiao Zhang; Xinyu Wang; Xinwen Zhang; Haoqi Liu; Xiaoying Zhang; Ziyi Yin; Yang Li; Xinhua Ding (Stress Biology, 2023)
Abstract Gray mold is a destructive disease caused by Botrytis cinerea, a pervasive plant pathogen, which poses a threat to both tomato growth and postharvest storage. The utilization of induced resistance presents a potential strategy for combating plant pathogenic attacks. ZNC (zhinengcong), an extract derived from the endophytic fungus Paecilomyces variotii, has been discovered to play a vital role in preventing diverse forms of bacterial infections. Nevertheless, the precise mechanism behind its ability to enhance tomato resistance to fungi remains unclear. In this study, we found that the exogenous spraying of ZNC could significantly improve the resistance of tomato plants to B. cinerea. The results of both the metabolomic analysis and high-performance liquid chromatography (HPLC) demonstrated that tomato plants responded to ZNC treatment by accumulating high levels of rutin. Additional transcriptome analysis uncovered that rutin enhances tomato resistance possible by initiating the generation of reactive oxygen species (ROS) and phosphorylation of mitogen-activated protein kinases (MPKs) related genes expression during the initial phase of invasion by B. cinerea. In addition, we also found that rutin might activate plant immunity by eliciting ethylene (ET) and jasmonic acid (JA)-mediated pathways. Therefore, plant immune inducer ZNC and rutin has bright application prospects and high utilization value to control gray mold. Graphical Abstract